2020
DOI: 10.1371/journal.pone.0227254
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the TORC2 gene promoter and their association with body measurement and carcass quality traits in Qinchuan cattle

Abstract: The TORC2 gene is responsible for nutrient metabolism, gluconeogenesis, myogenesis and adipogenesis through the PI3K-Akt, AMPK, glucagon and insulin resistance signaling pathways. Sequencing of PCR amplicons explored three novel SNPs at loci g.16534694G>A, g.16535011C>T, and g.16535044A>T in the promoter region of the TORC2 gene in the Qinchuan breed of cattle. Allelic and genotypic frequencies of these SNPs deviated from Hardy-Weinberg equilibrium (HWE) (P < 0.05). SNP1 genotype GG, SNP2 genotype CT and SNP3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…In our study, there was a significant association (p < 0.05) between the four InDels (FTO-2, FTO-3, FTO-5, PLIN1) we detected in FTO and PLIN1, with morphometric traits in the HS, DS, and STHS breeds. This result was similar to those of previous findings in other species, where mutations in these genes were significantly associated with the animals' growth traits [7,28,29]. The sheep industry in China has made significant progress in recent years and has primarily focused on fulfilling the daily demands of consumers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, there was a significant association (p < 0.05) between the four InDels (FTO-2, FTO-3, FTO-5, PLIN1) we detected in FTO and PLIN1, with morphometric traits in the HS, DS, and STHS breeds. This result was similar to those of previous findings in other species, where mutations in these genes were significantly associated with the animals' growth traits [7,28,29]. The sheep industry in China has made significant progress in recent years and has primarily focused on fulfilling the daily demands of consumers.…”
Section: Discussionsupporting
confidence: 90%
“…Identifying the causal variant of a gene can enhance the accuracy of genomic selection and is considered to be an efficient approach for analyzing the associations between genetic polymorphisms and economically important traits [29]. This study primarily focused on the association between mutations at the InDel locus and the morphometric traits in three sheep breeds; the traits varied within the breeds.…”
Section: Discussionmentioning
confidence: 99%
“…4) that the sequence isolates of this study were closely associated with each other and they showed sequence similarity with the reported strains of USA, Thailand, Uganda, Philippines, China, Uruguay and Zimbabwe. Moreover, multiple sequence alignment of the 16S ribosomal RNA gene sequences of 5 different clones of the A. marginale depicts substantial variation in the genotypes of A. marginale found in different locations of KP (Khan et al 2020). Liu et al (2005);Ferrolho et al (2016); Byaruhanga et al (2018) have conducted similar studies for the sequencing and phylogenetic characterization of A. marginale which correlate with this study.…”
Section: Discussionsupporting
confidence: 70%
“…The IL17A gene, on the other hand has been reported to activate PPARγ which is involved in increased adipogenesis 39 . In addition, NR4A receptor family in conjunction with CRTC2 and PPARγ assists in myogenesis and adipogenesis via the CREB pathway 40 . Thus, most of the highly connected genes identified in Bandur lambs were associated with growth, proliferation and adipogenesis.…”
Section: Discussionmentioning
confidence: 99%